2007
DOI: 10.1093/sleep/30.11.1503
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Measurement of Lateral Parapharyngeal Wall Thickness in Patients with Obstructive Sleep Apnea

Abstract: Sonographic measurement of LPW thickness is a novel and reliable technique and had good correlations with measurement by MRI and the severity of OSA. Ultrasound may provide an alternative imaging modality with easy accessibility and lower cost in OSA research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 20 publications
3
45
1
Order By: Relevance
“…Clinically BMI and NC have been known to be strong predictors of OSA [15,18,22,26]. In this study, patients with OSA had greater BMI than control group.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Clinically BMI and NC have been known to be strong predictors of OSA [15,18,22,26]. In this study, patients with OSA had greater BMI than control group.…”
Section: Discussionmentioning
confidence: 59%
“…Numerous studies report that OSA is closely related with anthropometric measurements obtained by diagnostic imaging techniques such as computed tomography (CT), magnetic resonance imaging, ultrasound imaging and lateral cephalography. [7,12,18,24,29].…”
Section: Introductionmentioning
confidence: 99%
“…Lahav et al [45] found that tongue base width, measured by ultrasound, may influence the severity of obstructive sleep apnea, including the patients' sensation of choking during night. Another important correlation, found by Liu et al [46], is the lateral parapharyngeal wall thickness. Further studies are still needed in this area.…”
Section: Airway Assessmentmentioning
confidence: 86%
“…Upper airway acoustic reflection provides limited information about the shape of the airway (54), but its use has not been standardized in children. Ultrasound is an important diagnostic radiological technique that currently has limited application for imaging the upper airway due to poor transducer-air coupling (55). A promising technique allowing quantitative imaging of upper airway anatomy and motion is real-time endoscopic optical coherence tomography.…”
Section: Evaluation Of the Upper Airway Using Imaging And Other Technmentioning
confidence: 99%